Assessment of Iraqi dental practitioners' and undergraduate students' knowledge regarding dentin hypersensitivity management: A cross-sectional study - Zaidoon Hasan Mohammed; Thanaa Ghani Nema; Sohaib Fadhil Mohammed; Hamsa Zaki Al-Assadi; Ala Mahdi Muhamed Ali; Aya Alaa Hussein (University Library System, University of Pittsburgh, 2024)
Objective: The characteristic of dentin hypersensitivity is brief, intense pain that results from exposed dentin in reaction to a variety of stimuli, including mechanical, thermal, osmotic, or chemical factors. This study aimed to evaluate the level of knowledge among undergraduate students and practicing dentists in Karbala City, Iraq, concerning the mechanisms, etiology, and treatment of dentin hypersensitivity (DH). Methods: 102 surveys were distributed via Google Forms to general practitioners and fourth- and fifth-year dental students at the Kerbala College of Dentistry in Iraq. The data were inputted into Microsoft Excel and analyzed using SPSS 22.0 for Windows as frequency distribution tables and figures. Results: Despite the differences in comprehension and expertise between students and dentists, a comparative analysis of their responses to various questions revealed several similarities. According to the survey, 28.8% of students reported that 10% of patients suffered from DH, while 32% of dentists reported the same. Additionally, 72% of dentists and 71.2% of students stated that DH is a severe problem for patients. Both dentists, 30%, and 26.9% of students, indicated that DH lasted for less than 2 weeks. According to dentists and students, females are more affected by DH (74%; n=37) and (71%; n=37), respectively. Conclusion: Students and dentists showed a similar level of knowledge on DH.